The moderating effect of gender on physical activity participation and physical fitness in children - Howard Gomwe; Lesego Phiri; Chioneso Show Marange (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2024)
Background: The level, direction or presence of the relationship between perceived physical activity (PA) participation and physical fitness (PF) in children may differ by gender and this will assist in designing gender-specific interventions to promote PA participation, which in turn improves PF levels.